2020
DOI: 10.3390/pr8050601
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Landfill Leachate Using Palm Oil Mill Effluent

Abstract: Sanitary landfilling is the most common method of removing urban solid waste in developing countries. Landfills contain high levels of organic materials, ammonia, and heavy metals, thereby producing leachate which causes a possible future pollution of ground and surface water. Recently, agricultural waste was considered a co-substratum to promote the biodegradation of organics in industrial wastewater. The use of low-cost and natural materials for wastewater treatment is now being considered by many researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It was indicated that each plant that acts as phytoremediation agent has its own efficiency rate in removing different pollutants. However, there are several factors that may affect the reduction percentage of contaminants, such as the type of pollutant and wastewater, treatment duration and pollutant concentration [52][53][54].…”
Section: Reduction Rate Of Codmentioning
confidence: 99%
“…It was indicated that each plant that acts as phytoremediation agent has its own efficiency rate in removing different pollutants. However, there are several factors that may affect the reduction percentage of contaminants, such as the type of pollutant and wastewater, treatment duration and pollutant concentration [52][53][54].…”
Section: Reduction Rate Of Codmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66] nitrogen, and other pollutants in the form of suspended particles and dissolved solid contaminants (8)(9)(10). Leachate has the potential to contaminate groundwater and the environment due to the high quantity of toxins it contains (8,11). Leachate typically has high Chemical Oxygen Demand (COD) values, ranging from 6000 to 60000 mg/L, and Biological Oxygen Demand (BOD) levels between 4000 and 13000 mg/L (12).…”
Section: Cite This Asmentioning
confidence: 99%
“…In the case of municipal solid waste disposal sites, leachate is generated during the process of decomposition of solid waste (Halim et al, 2017). The main problems associated with waste disposal sites are the production of leachate and release of harmful CH gas (Banch et al, 2020b). 4 The release of leachate from landfill in the environment is a concern due to toxic nature of leachate that can have deterioration effects on human health (Banch et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%